A comparative study of seed morphology in relation to desiccation tolerance and other physiological responses in 71 Eastern Australian rainforest species. Issue 1 (26th March 2012) - HAMILTON, KIM N.; OFFORD, CATHERINE A.; CUNEO, PETER; DESEO, MYRNA A.
Abstract Seed characteristics were measured in 71 Eastern Australian rainforest species representing 30 families. Sensitivity to desiccation to low moisture contents (< 10%) occurred in 42% of species. We estimate, based on findings from 100 species from this present study and previously published reports, that 49% of Eastern Australian rainforest species have non‐orthodox seeds. Germination level and time to 50% germination were not significantly different between desiccation sensitive (DS) and desiccation tolerant (DT) seeds. The estimation of seed desiccation sensitivity based on predictors is an important tool underpinning ex situ conservation efforts. Seed characteristics differed significantly between DS and DT seeds; that is, DS seeds had: (i) larger fruits (19 949 mg vs 8322 mg); (ii) larger seeds (1663 mg vs 202 mg); (iii) higher seed moisture contents (49.7% vs 35.5% fresh weight); (iv) lower oil content (7.3% vs 24.8% yield); and (v) less investment in seed coats (0.19 vs 0.48 seed coat ratio). Only 25% of DS seeded species had oily seeds compared with 87% of DT seeded species. Most green embryos were DS. Seed coat ratio was the best predictor of seed DS (80% correctly predicted). Seed moisture content at maturity was also related to germination time. Mean seed size was correlated (−0.657, P = 0.01) with mean seed oil content in 46 species. Further research on seed storage physiology of possible oily and/or DS seeded species is crucial to ensure future long‐term security of this biodiversity, particularly for species currently threatened in situ and/or of socioeconomic importance in Eastern Australian rainforests.